The Influence Of Competence And Work Productivity Of Inpatient Nurses On The Quality Of Healthcare Service Marketing At The Regional General Hospital Of Bogor City - Selfi Purnawirawati; Ratna Prayogi; Deviari Damaliata Soemarno; Marisi Pakpahan; Armein Sjuhary Rowi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the influence of the competence and work productivity of inpatient nurses on the quality of healthcare service marketing at RSUD Kota Bogor. Nurse competence is measured through indicators such as clinical knowledge, practical skills, effective communication, leadership, management, ethics, and professionalism. Meanwhile, nurse work productivity is assessed based on time efficiency, accuracy in medical procedures, and the ability to complete tasks effectively. The quality of healthcare service marketing is measured through service quality, patient experience, hospital image, communication, information, and service pricing. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to 60 respondents, consisting of patients and their families in the inpatient ward at RSUD Kota Bogor. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that nurse work productivity has a significant influence on the quality of healthcare service marketing, while nurse competence does not show a significant influence. Simultaneously, both nurse competence and work productivity significantly affect the quality of healthcare service marketing. Based on these findings, it is recommended that the management of RSUD Kota Bogor focus on improving nurse work productivity through workload adjustments, provision of adequate facilities, and time management training. Although nurse competence was not significant in this study, competence development remains important for overall service quality improvement. The implementation of a patient feedback system is also recommended to continuously enhance patient satisfaction and the quality of healthcare service marketing. Keywords: Nurse Competence, Work Productivity, Quality of Healthcare Service Marketing, RSUD Kota Bogor.